If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(p-7)=-3(4p+7)
We move all terms to the left:
-5(p-7)-(-3(4p+7))=0
We multiply parentheses
-5p-(-3(4p+7))+35=0
We calculate terms in parentheses: -(-3(4p+7)), so:We get rid of parentheses
-3(4p+7)
We multiply parentheses
-12p-21
Back to the equation:
-(-12p-21)
-5p+12p+21+35=0
We add all the numbers together, and all the variables
7p+56=0
We move all terms containing p to the left, all other terms to the right
7p=-56
p=-56/7
p=-8
| x/6=(x-7)/9 | | 2x-5+11=13+x | | -6m+2=-4m-6 | | 2.4x–6.4=3.8 | | 3x-7=-x+8 | | 50w+100=40w+250 | | x-4=1/5(6x-54) | | -19.98-10.5c=-8.2c+19.81 | | 2x-5+11=13=x | | 12v=432 | | 10n=5n+10 | | 42x+90=42x+4 | | 7=6x+6x+7 | | 2/5m-1/5=1/10 | | 7x-5(x-1)=-5+12x | | 1/6x=x+5 | | 392=28d | | 90-4d=d+3 | | 9–4u=1 | | 11x+-7=180 | | 5=7w+8w+w | | 4(x+5)=7x+15-3x+5 | | 6|5z+7|=30 | | (x+3)/9=5/6 | | 1+5w=16 | | -2.7x+2(0.4+3x)=2.8-1.2x | | 9b-3=8b-4 | | 11x=173 | | -3-3r=-5(r-5)-2r | | 14=-2x+18 | | 6=4n=15 | | y+57=609 |